Using Simulation and Case Studies Combined to Improve Student Knowledge: A Retrospective Study. Issue 3 (May 2017) - Sarasnick, Janice A.; Pyo, Katrina A.; Draper, Jason
Abstract: AIM: The aim of the study was to examine effects of high-fidelity simulation and computerized case studies in an advanced medical-surgical course. BACKGROUND: The challenges of coordinating clinical education and desire to utilize innovative methods of teaching were the impetus for course design. METHOD: A retrospective review compared HESI TM specialty exam scores for groups of the newer and former course design. In the newly configured course, students alternated weekly between simulation and computer-assisted case studies and traditional clinical experiences. RESULTS: Quantitative methods were utilized to analyze data; HESI specialty exam scores were determined to be statistically significantly higher for the groups of the newer design model. CONCLUSION: Incorporating case studies and high-fidelity simulation on a biweekly basis may be the reason for improved performance.